Atividade toxicogenética de corantes usados na formulação da tintura capilar preta, individuais e em associação, por meio de diferentes ensaios biológicos - Tafurt Cardona, Yaliana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
According to the International Agency for Research on Cancer (IARC), in vitro and in vivo assays (human populations exposed) have demonstrated that some dyes used in the coloring process can be considered as mutagenic and carcinogenic. Epidemiological studies in occupationally exposed people indicated an association with risk of bladder cancer and lymphoid malignancy. As well, the personal use of hair dyes has been associated to bladder cancer. Almost 33% of women, over 18 years and 10% of men, with more than 40 years, use some kind of hair dye. The black dye is a semipermanent colorant composed by mixture of several tinctures that include two pure colorants (Basic Red 51 and Basic Brown 17), both of these are azo-dyes (-N=N-), and a mixture known as Arianor Ebony, composed by other five dyes, among the are the azo-corants and anthraquinones (Basic blue 99, Basic brown 16, Acid violet 43, Basic red 76, and Basic yellow 57). The azo-corants are considered hazardous substances, due to production of aromatic amines on their degradation; these amines can be more toxic than the original compounds. The anthraquinones dyes are widely used for plastics staining and are known for their mutagenic, carcinogenic and toxic effects if ingested. The aim of this study was to evaluate the cytotoxicity (Thiazolyl Blue Tetrazolium Bromide test-MTT), genotoxicity (Comet assay and Micronucleus) of all corants that compose the black capillary dye, through tests performed with cellular cultures of human hepatome (HepG2), as well as the evaluation of mutagenic properties of the mixture (Ames test), using Salmonella typhimurium. Also, was evaluated the expression of 7 different apoptose genes. The results obtained in this study has demonstrated that the Basic Red 51 (BR51), Basic Brown 17 (BB17), Arianor Ebony and the capillary mixture of dyes induced genotoxic effects on the exposed cells, including the DNA fragmentation and the formation of the MN. The ...

Segundo a Agência Internacional para Pesquisa do Câncer (IARC), estudos utilizando ensaios in vitro e in vivo (populações humanas expostas) demonstraram que algumas tinturas de cabelo e muitos produtos químicos utilizados no processo de tingimento capilar podem ser considerados mutagênicos e carcinogênicos. Estudos epidemiológicos em pessoas expostas ocupacionalmente a tinturas de cabelo indicaram uma associação com risco de câncer de bexiga e neoplasias linfoides. Da mesma forma, o uso pessoal de corantes capilares permanentes foi associado com câncer de bexiga. Cerca do 33% das mulheres, com mais de 18 anos de idade e 10% dos homens com mais de 40 anos, usam algum tipo de corante de cabelo. A tintura capilar preta é uma coloração semipermanente, que é composta por uma mistura de vários corantes, incluindo dois corantes puros (Basic red 51 e Basic brown 17), ambos azo corantes (- N=N-) e uma mistura, denominada Arianor Ebony, composta por cinco corantes, dentre eles azo corantes e antroquinonas (Basic blue 99, Basic brown 16, Acid violet 43, Basic red 76, and Basic yellow 57). Os azo corantes são considerados substâncias perigosas, pois a sua degradação gera produtos como aminas aromáticas que podem ser mais tóxicas que os compostos originais. Os corantes de antraquinona são amplamente utilizado para a coloração de plásticos e tintas industriais conhecidos por serem mutagênicos, carcinogênicos e tóxicos por via oral. Este projeto de pesquisa teve como objetivo geral avaliar a citotoxicidade (teste do Thiazolyl Blue Tetrazolium Bromide- MTT), genotoxicidade (ensaios de Cometa e Micronúcleos) de todos os corantes que compõem a tintura capilar preta, por meio de ensaios realizados com cultura de células de hepatoma humano (HepG2), assim como também avaliar a mutagênicidade da mistura (teste de Ames), pelo teste com Salmonella typhimurium nas linagens TA98 e TA100. Também foi avaliada a expressão de 7 diferentes...
Keywords: Molecular biology; Biologia molecular; Toxicidade - Testes; Citotoxicidade; Toxicologia genética; Mutagenese; Corantes e tingimento; Corantes